2011
DOI: 10.1371/journal.pone.0018773
|View full text |Cite
|
Sign up to set email alerts
|

Latency Antigen α-Crystallin Based Vaccination Imparts a Robust Protection against TB by Modulating the Dynamics of Pulmonary Cytokines

Abstract: BackgroundEfficient control of tuberculosis (TB) requires development of strategies that can enhance efficacy of the existing vaccine Mycobacterium bovis Bacille Calmette Guerin (BCG). To date only a few studies have explored the potential of latency-associated antigens to augment the immunogenicity of BCG.Methods/Principal FindingsWe evaluated the protective efficacy of a heterologous prime boost approach based on recombinant BCG and DNA vaccines targeting α-crystallin, a prominent latency antigen. We show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…This heterologous prime boost regimen provides a superior and extended protection against M. tuberculosis infection in guinea pigs as well as in mice. According to our previous findings, α-crystallin based DNA vaccine, although, failed to surpass the protection conferred by BCG vaccine, when used as a standalone vaccine [14], it is was able to substantially improve the protection conferred by a recombinant BCG vaccine over-expressing this antigen [15]. Our current findings are thus, all the more important as they signify that the meager immune responses generated by BCG specific to α-crystallin can be substantially boosted by this DNA vaccine resulting in enhanced and extended protection superior to BCG.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This heterologous prime boost regimen provides a superior and extended protection against M. tuberculosis infection in guinea pigs as well as in mice. According to our previous findings, α-crystallin based DNA vaccine, although, failed to surpass the protection conferred by BCG vaccine, when used as a standalone vaccine [14], it is was able to substantially improve the protection conferred by a recombinant BCG vaccine over-expressing this antigen [15]. Our current findings are thus, all the more important as they signify that the meager immune responses generated by BCG specific to α-crystallin can be substantially boosted by this DNA vaccine resulting in enhanced and extended protection superior to BCG.…”
Section: Discussionmentioning
confidence: 89%
“…We showed that this DNA vaccine induces Th1 response and protects guinea pigs against M. tuberculosis infection, even though, it could not surpass the protective efficacy of BCG, when employed alone in a prophylactic mode [14]. Recently, we also showed that DNAacr efficiently boosts the immunity following vaccination with a recombinant BCG vaccine over-expressing α-crystallin [15]. However, as majority of global population represents BCG vaccinated individuals, in this study, we have evaluated the ability of a booster DNA vaccine expressing α-crystallin to strengthen the immune responses and enhance and prolong the protective efficiency of BCG.…”
Section: Introductionmentioning
confidence: 99%
“…This protein exhibits several properties, such as refolding ability, aggregation prevention ability, etc., that are associated with other sHSPs. Direct implications of chaperone function of acr1 mycobacterial sHSP (M. tuberculosis HSP16.3) on the survival and virulence of M. tuberculosis pathogen are well documented in the literature [66,67]. Because HSP18S 52 prevents the aggregation of various stressed protein and helps E. coli to survive under thermal stress, the chaperone ability of HSP18S 52 may play an important role in the survival of M. leprae pathogen in the host.…”
mentioning
confidence: 99%
“…We also showed that DNAacr conferred a superior protection than BCG vaccination when employed either in ‘rBCG prime – DNA boost’23 or ‘BCG prime – DNA boost’24 regimen. In this study, we have evaluated the immunotherapeutic potential of adjunctive immunotherapy with DNAacr and DNAsod in a murine model of latent TB to shorten the duration of chemotherapy and to prevent the reactivation of latent infection.…”
mentioning
confidence: 63%